The role of managerial ownership, independent commissioners, and corporate social responsibility, moderated by enterprise risk management, on company value in the pharmaceutical industry listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022 - Hamzah Abdul Aziz Wiradikusumah (Eduvest - Journal of Universal Studies, 2024)
This study aims to investigate the influence of Managerial Ownership, Independent Commissioners, and Corporate Social Responsibility, both partially and collectively, with Enterprise Risk Management moderation on Company Value. Company value is measured using Tobins'q method. The research was conducted in the Pharmaceutical Industry listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The research method used is quantitative. The population of the study consisted of 11 companies. Samples were determined using purposive sampling technique, obtaining samples from 10 companies with 5 years of observation, resulting in 50 samples. Hypothesis testing analysis was conducted using Moderated Regression Analysis (MRA) with SPSS 25.0 software for Windows. The results of the study indicate that: 1) Managerial Ownership has a negative and non-significant partial effect on Company Value, 2) Independent Commissioners have a positive but non-significant partial effect on Company Value, 3) Corporate Social Responsibility has a positive and significant partial effect on Company Value, 4) Enterprise Risk Management moderates positively but non-significantly the effect of Managerial Ownership on Company Value, 5) Enterprise Risk Management moderates positively and significantly the effect of Independent Commissioners on Company Value, 6) Enterprise Risk Management moderates positively and significantly the effect of Corporate Social Responsibility on Company Value, 7) Managerial Ownership, Independent Commissioners, Corporate Social Responsibility together with Enterprise Risk Management moderation have a significant effect on Company Value.